Synthesis, Antimicrobial Activity, Molecular Docking and ADMET Study of a Caprolactam-Glycine Cluster - Çelik, Sefa; Albayrak, Ali Tuğrul; AKYÜZ, SEVİM; Özel, Ayşen E.; Sığırcı, Belgi Diren (Taylor & Francis Inc., 2021)
Density functional theory calculations were performed with DFT method using both b3lyp/6-311++G(d,p) and wb97xd/6-311++G(d,p) levels of theory to predict the molecular geometry, to evaluate the molecular electrostatic potential and frontier molecular orbitals of synthesized a new compound: caprolactam-glysine cluster (CL-Gly). Molecular docking study of the CL-Gly was carried out to clarify the interaction and the probable binding modes, between the title compound and DNA. The antibacterial activities of CL-Gly cluster against Gram-positive and Gram-negative bacteria was determined. In silico ADMET study was also performed for predicting pharmacokinetic and toxicity profile of the synthesized cluster which expressed good drug-like behavior and non-toxic nature. It was revealed that the compound has importance in drug discovery process. Communicated by Ramaswamy H. Sarm
Keywords: Antimicrobial Activity; Caprolactam; DFT Calculations; Glycine; Molecular Docking